Dinamika deforestasi dan degradasi hutan di Provinsi Papua - Febi Selvandy Putri, Eka; Murdjoko, Agustinus; Raharjo, Syafrudin (Cassowary, 2024)
ABSTRACT: The dynamics of the change in forest cover and its impact on carbon dioxide emissions in Papua Province over the 32 years, from 1990 to 2022. The research was carried out from April to May, using secondary data consisting of land cover maps, slopes of slope, and forest function on a scale of 1:250.000 and administrative territory boundaries on a scale of 1:50.000. The analysis methods involve codification processes, map overlay, land cover change analysis, and CO2 emission calculation. Research results show that during the period, Papua Province suffered significant deforestation. Deforestation was recorded at 256.065 ha at an average rate of 8.002 ha/year, while forest degradation reached 965.955 ha with an average speed of 30.186 ha/year. Further analysis shows that Sarmi district is the region with the highest level of damage, with deforestation of 35.507 ha and forest degradation of 292.860 ha. The impact of deforestation and forest degradation on carbon dioxide emissions is also very significant. Deforestation accounts for about 174.720.433 tons of CO2, with an annual average of 5.460.014 tons of CO2/year, while forest degradation contributes about 193.584.910 tons of CO2, with an average yearly of 6.049.528 tons of CO2/year. Deforestation and forest degradation in Papua Province are complex and interrelated. The leading causes are economic, mining, and social factors. As a result, these findings suggest that the Papua Province needs better forest conservation and management measures and the development of sustainable policies to maintain the sustainability of forest ecosystems and reduce greenhouse gas emissions.